THE EFFECT OF NUMBERED HEAD TOGETHER (NHT) COOPERATIVE LEARNING MODEL ON LEARNING OUTCOMES - Nur Afifa; A. Lilis Kurniah; Arif Firmansyah (Universitas Tadulako, 2021)
This study examined the Effect of Numbered Head Together (NHT) Cooperative Learning Model on the Learning Results of Students at Sirenja. The sample of this research was all students amounting to 15 people. Data collection in this study used tests, observation and documentation. The data collected was then analyzed by testing the hypothesis using the t-test. The results showed that the average value of student learning outcomes before being given treatment was 55.67 and after being given treatment was 77.67 this indicates an increase in student learning outcomes. If this value is entered into the t-score statistical test, the t-count value is 3.115. If t count is consulted in table t with a sample size of 15 using a significant level of 5% (ɑ = 0.05) at degrees of freedom (db) = N - 1 = 15 - 1 = 14, the t table value is 1.761, it can be seen that the t value greater than t table or 7,062> 1,761. Thus, Ho is rejected and Ha is accepted, which means that there is a significant difference between learning outcomes before being given treatment and after being given treatment using the NHT type learning model or it can be said that there is an effect of Numbered Head Together (NHT) Cooperative Learning Model on Learning Outcomes.